The Berenstain Bears down on the farm - Berenstain, Stan, 1923-2005; Berenstain, Jan, 1923-2012 (New York : HarperCollins, 2006)
The Berenstain Bears visit Farmer and Mrs. Ben's farm and learn about their life there.
"1, beginning reading."
004-008.
Keywords: Berenstain Bears (Fictitious characters) -- Juvenile fiction; Farm life -- Juvenile fiction; Bears -- Juvenile fiction; Berenstain Bears (Fictitious characters) -- Fiction; Farm life -- Fiction; Bears -- Fiction; Stories in rhyme